An Antioxidant Nanoparticle Enhances Exercise Performance in Rat High‐intensity Running Models. Issue 10 (4th March 2021) - Toriumi, Takuto; Kim, Ahram; Komine, Shoichi; Miura, Ikuru; Nagayama, Suminori; Ohmori, Hajime; Nagasaki, Yukio
Abstract: Although the adverse effects of excessively generated reactive oxygen species (ROS) on the body during aerobic exercise have been debated, there are few reports on the remarkable effects of the application of conventional antioxidants on exercise performance. The conventional antioxidants could not enhance exercise performance due to their rapid excretion from the body and serious adverse effects on the cellular respiratory system. In this study, impact of the original antioxidant self‐assembling nanoparticle, redox‐active nanoparticle (RNP), is investigated on the exercise performance of rats during running experiments. With an increase in the dose of the administered RNP, the all‐out time of the rat running extends in a dose‐dependent manner. In contrast, with an increase in the dose of the low‐molecular‐weight (LMW) antioxidant, the all‐out running time of the rats decreases. The control group and LMW antioxidant treated group decrease in the number of red blood cells (RBCs) and increase oxidative stress after running. However, the RNP group maintains a similar RBC level and oxidative stress as that of the sedentary group. The results suggest that RNP, which shows long‐blood circulation without disturbance of mitohormesis, effectively removes ROS from the bloodstream to suppresses RBC oxidative stress and damage, thus improving exercise performance. Abstract : Antioxidant self‐assembling nanoparticle (RNP), which shows long‐blood circulation without disturbance of mitochondrial dysfunction, is developed. RNP inhibits the negative vicious cycle of high‐intensity running‐induced hemolysis, iron release, ROS production, oxidative stress in red blood cell and skeletal muscle, and further hemolysis, thus improving exercise performance in a dose‐dependent manner.